Evaluation of Boiler Feed Water Quality in Tofu Industry UD. FIT in Bocek Village - Prihardani, Fitri; Fariana, Nida; Yogaswara, Rachmad Ramadhan; Islamiyah, Syuaibatul (UPN Veteran Jatim, 2024)
The UD FIT industry, situated in Bocek Village, Karangploso District, operates as a tofu factory employing modern equipment, including a fire tube boiler. The quality of feed water utilized in the boiler is essential for optimizing its efficiency. This study aimed to analyze the boiler feed water sourced from household wells at UD FIT's tofu factory, using various indicators such as turbidity, iron content, total dissolved solids (TDS), hardness, and pH levels. The test results revealed a temperature of 26°C, TDS of 253 mg/L, turbidity of 4.74 NTU, iron content of 1.123 mg/L, hardness of 180.5 mg/L, and pH of 7.89, with no detectable odor, color, or taste. Based on these findings, it is concluded that the boiler feed water utilized by UD FIT generally meet the quality standards, except for the pH parameter, which is not in accordance with the standard.